2018
DOI: 10.1080/09688080.2018.1484220
|View full text |Cite
|
Sign up to set email alerts
|

Wealthy, urban, educated. Who is represented in population surveys of women’s menstrual hygiene management?

Abstract: Inadequate menstrual hygiene presents a barrier to women's dignity and health. Recent attention to this marginalised challenge has resulted in the first national assessments of menstrual practices. Intuitively, surveys require women to have had a recent menses to be eligible. This study seeks to determine if there are demographic differences between women who are eligible and ineligible to answer questions about their menstrual hygiene during these assessments. Secondary analyses were undertaken on nationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Outside of a few key papers that highlight the menstrual experiences of women in the workplace, emergency context, or vaginal bleeding throughout the life course, experiences of menstruation among adult women and outside of school settings remains underexplored [38, 39, 43, 70]. This research confirmed that women need tangible support to manage menstruation, however we uncovered needs for MHM that extend beyond those identified in the JMP definition.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Outside of a few key papers that highlight the menstrual experiences of women in the workplace, emergency context, or vaginal bleeding throughout the life course, experiences of menstruation among adult women and outside of school settings remains underexplored [38, 39, 43, 70]. This research confirmed that women need tangible support to manage menstruation, however we uncovered needs for MHM that extend beyond those identified in the JMP definition.…”
Section: Resultssupporting
confidence: 54%
“…Moreover, this research gives voice to the experiences of rural women who are underrepresented in studies on menstruation. In an analysis of data across eight countries (including India) from the Performance Monitoring and Accountability 2020 survey programme, Hennegan et al (2018) found that women who were wealthy, urban, educated, young, and unmarried were more likely to be eligible to answer questions about menstruation, resulting in an underrepresentation of data from rural, older, less educated, and married women [70].…”
Section: Discussionmentioning
confidence: 99%
“…Household level of wealth was derived from the ownership of various assets, building material used for the primary residence, and access to water and sanitation facilities. Wealth quintiles are then calculated and reported by the primary data collectors [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of this sub-sample compared to the full population of women across PMA2020 surveys are discussed in more detail elsewhere. 30 Further details regarding the PMA2020 surveys are published elsewhere, 29 and available on the survey programme website.…”
Section: Pma2020mentioning
confidence: 99%